2015
DOI: 10.1002/14651858.cd006850.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Braces for idiopathic scoliosis in adolescents

Abstract: Due to the important clinical differences among the studies, it was not possible to perform a meta-analysis. Two studies showed that bracing did not change QoL during treatment (low quality), and QoL, back pain, and psychological and cosmetic issues in the long term (16 years) (very low quality). All included papers consistently showed that bracing prevented curve progression (secondary outcome). However, due to the strength of evidence (from low to very low quality), further research is very likely to have an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
78
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(79 citation statements)
references
References 166 publications
1
78
0
Order By: Relevance
“…Numerous conservative techniques have been used to treat AIS, such as acupuncture, braces, electrical stimulation, exercises, foot orthosis, osteopathy, and yoga. The most recent systematic review on braces for AIS reported long-term stability in terms of back pain (very low quality evidence) in addition to a similar outcome for quality of life and psychological and cosmetic issues [ 39 ]. The authors highlighted that performing a meta-analysis was not possible due to differences among the studies.…”
Section: Adolescent Idiopathic Scoliosis (Ais) and Back Painmentioning
confidence: 99%
“…Numerous conservative techniques have been used to treat AIS, such as acupuncture, braces, electrical stimulation, exercises, foot orthosis, osteopathy, and yoga. The most recent systematic review on braces for AIS reported long-term stability in terms of back pain (very low quality evidence) in addition to a similar outcome for quality of life and psychological and cosmetic issues [ 39 ]. The authors highlighted that performing a meta-analysis was not possible due to differences among the studies.…”
Section: Adolescent Idiopathic Scoliosis (Ais) and Back Painmentioning
confidence: 99%
“…Corrective surgery is invasive, and it is accompanied by non-negligible risks of complications. Bracing can be used to efficiently slow down or stop the progression, and patients often prefer it to observation [2,3]. Early detection of progressive curves offers the opportunity to undergo effective, non-operative treatments to the patients, thus reducing the need of surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Treatment indications for scoliosis continue to be under debate [ 9 , 10 ]. Conservative treatment of scoliosis, both rehabilitative exercise and bracing, are recognized in literature reviews [ 11 - 14 ], Cochrane reviews [ 15 , 16 ] and randomized controlled studies [ 17 - 19 ]. Often, when a scoliosis reaches 45- 50º, surgery is the typical mode of treatment despite the absence of high-quality evidence [ 9 , 14 , 20 - 25 ].…”
Section: Introductionmentioning
confidence: 99%